Protective role of melatonin in ultraviolet radiation- induced oxidative stress in human skin photoaging - Suyanto, Maria Veronica Putri; Widianti, I Gusti Ayu (Faculty of Medicine, Universitas Trisakti, 2023)
The ultraviolet radiation of the sun that reaches the earth is made up of ultraviolet A (95%) and ultraviolet B (5%). Exposure to ultraviolet radiation (UVR) is the main factor in photoaging. Chronic exposure to sunlight acts as an environmental stressor, leading to oxidative damage or stress. Oxidative damage stimulates the accumulation of free radicals, such as reactive oxygen species (ROS) or reactive nitrogen species (RNS) that are responsible for premature skin aging. Photoaged skin is characterized externally by irregular pigmentation, wrinkles, and reduced skin elasticity, and internally by the breakdown of dermal collagen and elastin. Free radicals can be scavenged and the skin can be protected from further oxidative damage by antioxidants. Melatonin is a hormone produced mainly by the pineal gland, as well as many other organs, including the skin. One of the functions of melatonin is exerted by the antioxidative melatoninergic system to prevent ultraviolet (UV)-induced skin photoaging. The aim of this review was to study the protective effect of melatonin on skin photoaging resulting from UVR exposure. The references were tracked using various databases, such as Google Scholar and PubMed with regard to publications in English for the last 5 years (2019-2023). Melatonin inhibits UVR-induced aging in multiple ways, such as protecting skin cells, binding free radicals, accelerating the activity of antioxidant enzymes, preventing increased mitochondrial membrane permeability, and assisting electron transport efficiency in the mitochondrial respiratory chain. Exogenous application of melatonin is usually by the oral route, but for localized effects on the skin, topical administration is recommended, with consideration of preparations with a better half-life and bioavailability. Understanding the protective antioxidant function of melatonin in UV-induced skin photoaging helps to optimize its application. The protective properties of melatonin against UVR-oxidative stress-induced photoaging will be further explored in this review.